Essays on energy poverty in Brazilian households - Silva, Lucas Adriano (2024)
Energy is essential in people's lives, necessary for daily activities such as cooking, watching television, and lighting environments. Therefore, the lack of access to clean, safe, and reliable energy constitutes a concerning issue known as energy poverty. Despite advances in recent decades in access to electricity and cooking gas, many Brazilian households still face energy vulnerability, a situation that can exacerbate food insecurity. This study measured energy poverty in Brazil, considering its multidimensional aspect, different localities, and the most vulnerable family arrangements. The research used the Multidimensional Energy Poverty Index (MEPI) to assess energy poverty, considering dimensions such as fuel use for cooking, final energy use, energy quality, and the ability to pay for electricity. To analyze the impact of the high share of electricity costs on food insecurity, binary and ordinal logistic models were used, along with the instrumental variables method to address potential endogeneity in the model. The results indicated that about 11.7% of Brazilian households are in a situation of energy poverty, with this figure rising to 30.7% in rural areas. Families with children and female headed single parent families are the most vulnerable in terms of the incidence and severity of energy poverty. The analysis showed a significant positive causal relationship between energy poverty and food insecurity. Households facing energy vulnerability are 43.1% more likely to transition from food security to mild, moderate, or serious food insecurity and 43.9% more likely to progress to moderate or serious food insecurity. Even after testing different strategies, the effect of energy vulnerability on food insecurity remained positive and significant. These findings provide a better understanding of energy vulnerability in Brazil, both in terms of its distribution and its impact on families. Keywords: energy poverty ; vulnerability ; electricity ; food insecurity ; Brazil.